EARLY DIAGNOSIS AND SPECIES DIFFERENTIATION IN MULTI DRUG RESISTANT-TUBERCULOSIS BY NESTED POLYMERASE CHAIN REACTION TARGETING HUP B GENE - DR SURAJEET KUMAR PATRA; DR ANJU JAIN; DR B L SHERWAL; DR ASHWANI KHANNA (International Journal of Pharma and Bio Sciences, 2010)
Introduction: Early diagnosis and prompt treatment of tuberculosis is the need of the time to prevent the morbidity and mortality related to it. The diagnosis of tuberculosis by conventional methods(culture) are time consuming. Objectives - Early diagnosis of tuberculosis by using molecular method (PCR) targeting hup B gene and to find out whether M.bovis could be a cause of MDR-TB or not . Materials and Methods: 50 MDR-TB patients were enrolled in our study after informed written consent. After processing the samples by Universal Sample Processing (USP) method, two step nested PCR was performed using two sets of primers (N1S1 & CTFR) of hupB gene. The amplicons were resolved on 8 % Polyacrylamide gel electrophoresis (PAGE), stained with ethidium bromide and viewed in a gel documentation system. Results: In our study, we observed that 86 % of patients have positive PCR assay for hup B gene. Of the total 43 patients those were positive in PCR assay for hup B gene; all (43) were infected with Mycobacterium tuberculosis. None of the patients were infected with Mycobacterium bovis. Conclusion - PCR targeting hup B gene can be used for early diagnosis of tuberculosis and it has the added advantages of differentiating between Mycobacterium tuberculosis and Mycobacterium bovis.